The Vulnerability of Bycacth Tuna of Handline Fishing in Southern Indian Ocean: Recorded in Sendang Biru Landing Port-Malang: Kerentanan Bycatch Tuna Dari Perikanan Handline di Selatan Samdera Hindia: Pencatatan Pelabuhan Sendang Biru-Malang - Yonvitner Yonvitner; Rahmat Kurnia; Mennofatria Boer; Helmy Akbar; Surya Gentha Akmal (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2020)
Bycatch tuna is an important commercial fish commodity in the Indian Ocean tuna fishery. Tuna bycatch fishing activity also has an impact on the decline in stocks, making it vulnerable and potentially unsustainable. This study aims to analyze the level of vulnerability of tuna side-caught fish, which was conducted in Sendangbiru Malang in July 2013. Vulnerability analysis using the Euclidean distance approach with productivity and susceptability data using PSA software. The catch of bycacth tuna is skipjack tuna (Katsuwonus pelamis), lemadang fish (Coryphaena hippurus), baby tuna (Thunnus albacores). The results of the vulnerability analysis showed that the level of vulnerability obtained was 1.66 for baby tuna, 1.27 for lemadang and 1.42 for skipjack. Overall, the vulnerability index value is still low from 1.8 where the stock is classified as low susceptibility and the potential for tuna bycatch is still potentially sustainable and does not lead to overfishing.